A case report of aggressive course of CD30+ primary cutaneous anaplastic large cell lymphoma. Issue 18 (7th May 2021) - Lyu, Wen-Tian; Song, Qi-Bin; Qiong, Wang; Liu, Jing; Yong, Ren; Yi, Feng-Tao; Han, Dong-liang
Abstract: Introduction: CD30+ primary cutaneous anaplastic large cell lymphoma (PC-ALCL) is a rare T-cell neoplasm, and has been reported to present with an indolent behavior. The PC-ALCL with aggressive behavior has not been reported in the literature. Patient concerns: We treated a patient with PC-ALCL that exhibited indolent behavior in the past 2 years and aggressive behavior within the last 3 months before presentation. Diagnosis: Aggressive CD30+ primary cutaneous anaplastic large cell lymphoma. Interventions: The radiotherapy regimen was individualized in terms of the target volume delineation and dose prescription, and the dose–response relationship was evaluated. Outcomes: The mean distance of microscopic infiltration was 14.1 mm in depth and 14.3 mm circumferentially. The lesion completely regressed after the delivery of 40 Gy in 20 fractions over 4 weeks. The tumor did not recur over the next year. Conclusion: An aggressive disease course is rare for indolent CD30+ PC-ALCL, which has similar histopathological characteristics as indolent PC-ALCL. The radiotherapy strategy should be individualized with curative intent.